Thermophysical and electrochemical properties measurements of novel choline-based ionic liquids - Lee, Tommy Hoong Wy (2025)
The urgent need for sustainable energy storage propels the search for advanced battery technologies. Traditional lithium-ion batteries with liquid electrolytes pose safety risks like flammability and leakage. Choline-based ionic liquids (ILs) incorporated into gel polymer electrolytes (GPEs) offer a promising solution with the potential to enhance safety, cost-effectiveness, and environmental sustainability. This thesis focuses on the development and optimization of choline-based IL GPEs specifically for lithium battery applications.